Teachers induction practices in secondary schools of Ethiopia - Yacob, Ephrem Tekle (2018)
The main purpose of the study was to investigate the practice of teachers’ induction in secondary schools of Ethiopia. The data was collected from Addis Ababa City Administration (AACA), Amhara Regional Stats (ARS), and Benishangul Gumuz Regional State (BGRS). These sites were selected according to the criterion of maximal variation. A total of 76 mentors, 95 Newly Qualified Teachers (NQTs), and 23 education personnel took part in the study using concurrent multilevel sampling design. The methodology is mixed; pragmatism as a philosophical assumption, and convergent parallel design as a strategy. The finding indicates that the awareness of a significant number of the research participants towards the teachers’ induction program is high. However, there are also individual teachers and education personnel who are left behind, which may affect the practice of induction and the learning of students. Moreover, the outcome of the practice of induction regarding turnover, increment of the commitment of teacher, improvement of classroom practice, and achievements of students was found to be limited. Significant numbers of NQTs begin teaching without the feeling of adequate preparation. Moreover, during their early induction period, they go through the feelings of loneliness, lost and insecurity. Significant portion of them were also left alone to integrate themselves with the school system. The support scheme lacks diversity and extrinsic motivation/impetus. However, both mentors and mentees consider mentoring positively, even though this needs to be revisited since there is a lack of flexibility in the use of newly emerging mentoring modalities. Among other things, a centralized approach of induction, guided by a single module all over the nation, hampered incorporating newly emerging needs of the NQTs. The support system also suffers from disparity among the research sites in which AACA provide more support to NQTs than the other regions. Work load, classroom management and students’ discipline have been identified as the main challenges of NQTs. The challenges of induction mainly emanated from the recruitment of individuals who lack both interest and competency accompanied by centralised induction modality which has been in use for more than a decade without updating. We can abridge that the practice of induction in secondary schools of Ethiopia is weak. The recruitment of competent and interested individuals for the teaching profession should be underlined and cemented by providing adequate support both during pre-service and in-service programs. The in-service support system should start with individually tailored induction program.
Keywords: Hochschulschrift